Prevalence of nutritional inadequacy in children aged 12-36 months: EPACI Portugal 2012 - Nazareth, M (2023)
Adequate nutritional intake in the first years of life is crucial for future health. The purpose of this study is to assess the adequacy of nutritional intake in Portuguese toddlers. The EPACI Portugal 2012 is a cross-sectional study of a representative sample of toddlers (n = 2230), aged between 12 and 36 months. Data on diets were collected by trained interviewers. The current analysis included 853 children with full data from 3-day food diaries completed by parents/caregivers. Intakes of energy, macro- and micronutrients were estimated through Statistical Program to Assess Dietary Exposure (SPADE). Nutritional adequacy was evaluated using Dietary Reference Values established by the European Food Safety Authority. A large proportion of children exceeded the recommended energy intake. The median daily protein intake was 4.7 g/kg/day, five times more than that recommended. About 9% and 90% of the children consumed a lower proportion of energy than the lower limit of the Reference Intake range for carbohydrates and fat, respectively. Around a third consumed less fibre and magnesium and 100% less vitamin D than the recommended Adequate Intake (AI). Almost a third consumed less vitamin A than the recommended Average Requirement (AR) and 86% of the children showed excessive sodium consumption. Portuguese toddlers consumed a low proportion of energy from fat, had energy and protein intakes above the recommendations and excessive intakes of sodium, and inadequate intakes of vitamin A. Every child consumed less than the recommended AI for vitamin D.